Correcting misinformation about the Russia-Ukraine War reduces false beliefs but does not change views about the War. - Ethan Porter; R Bailey Scott; Thomas J Wood; Raushan Zhandayeva (PLoS ONE)
We report results from simultaneous experiments conducted in late 2022 in Belarus, Estonia, Kazakhstan, Russia and Ukraine. The experiments focus on fact-checking misinformation supportive of Russia in the Russia-Ukraine War. Meta-analysis makes clear that fact-checking misinformation reduces belief in pro-Kremlin false claims. Effects of fact-checks are not uniform across countries; our meta-analytic estimate is reliant on belief accuracy increases observed in Russia and Ukraine. While fact-checks improve belief accuracy, they do not change respondents' attitudes about which side to support in the War. War does not render individuals hopelessly vulnerable to misinformation-but fact-checking misinformation is unlikely to change their views toward the conflict.